TINGKAT EKONOMI TERHADAP MINAT IBU DALAM PEMBERIAN ASI EKSKLUSIF PADA BAYI USIA 0 – 6 BULAN DI PONKESDES SALEN KECAMATAN BANGSAL KABUPATEN MOJOKERTO - Dyah Siwi Hety (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2018)
The government is currently promoting to give breastmilk exclusively. Nielson findings in urban areas in Indonesia shows that in giving breastmilk exclusively has relationship to the economical ability of the family. The purpose of this study is to determine the relationship of the economical level of mothers’ interest in giving the exclusive breastmilk mothers to infants aged 0-6 months. Design of this study is an analitical observation with cross sectional. The population in this study is 37 mothers who have infant aged 0-6 mothers and taken by 34 respondent as sample. The sampling technique used is probability sampling type cluster random sampling. It had been conducted in Desa Salen, Bangsal- Mojokerto, on November 2017 – January 2018. Collecting data uses a questionnaire. The data processing use editing, coding, scoring, tabulating performed with Spearman rho test. The results show that the level of economical upper classes tend to have a low interest in giving exclusive breastmilk consist of 10 respondent (29.4%) and respondents with lower economical levels tend to give exclusive breastmilk consist of 2 respondents (5.9%). Based on Spearman rank test, it is obtained by value ρ = 0,0001 with significance level on a = 0,05. So,the value is ρ < a, H1 is accepted that it the economical level of mothers interest has relationship with giving exclusive breastmilk to infants aged 0-6 month. Most of respondents who have income more than Rp. 2.000.000 tend to have low interest in giving exclusive breastmilk because of their high income. They prefer to give their babies formula milk for their sufficient nutrition. The midwives can provide breastfeeding mothers motivation with counseling, distributing leaflets, visiting their houses in order to prepare giving exclusive breastmilk optimally